Energy Audit - Optimization of Energy Losses and Load Management of Textile Industry in Pakistan: Energy Audit - Optimization of Energy Losses and Load Management of Textile Industry in Pakistan (European journal of volunteering and community-based projects, 2021)
Energy is one of the main arguments in favor of evaluating the procedure, promotion, and presence of the world. Energy audit and conservation is important for the natural and economic progress of developing countries such as Pakistan. In this research work, energy audit and load management were carried out for efficient energy utilization in industrial processes. Energy audit conducted in the spinning unit of Nishat textile industry proved beneficial in realizing efficient utilization of energy along with reduction in energy waste. A detailed comparison of newly installed and rewound induction motors, air compressor systems, and lighting systems was performed. Energy utilization of rewound induction motors, using BEST energy saving software, and lighting was also analyzed. Upon completion of the energy audit total annual electrical energy 31,983. MWh utilization was reduced to 30,462. MWh. After energy audit annual 4.75% MWh per annum electrical energy saved was proposed to be saved. This energy audit will ensure the minimization of cost factor, improved efficiency, proper management of operating load, and energy losses in the audited textile industry.